2021
DOI: 10.18203/2320-6012.ijrms20213677
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of early T-cell precursor acute lymphoblastic leukemia among immunophenotypically categorised acute T-cell lymphoblastic leukaemia cases

Abstract: Acute lymphoblastic leukaemia is the most common hematopoietic malignancy in childhood, comprising of B-cell lineage (85%) and T-cell lineage (15%). Recent studies have identified a subtype of T-cell acute lymphoblastic leukaemia (T-ALL) termed “early T-cell precursors (ETP)” recognised as a new provisional entity in 2016 update to the World Health Organization (WHO) classification of acute leukaemia, early T-cell precursor acute lymphoblastic leukemia (ETP-ALL) is characterized by a unique immunophenotype and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In this study Hb was significantly higher after chemotherapy with an average moved from 7.6 to 11.0 mg/dl. This result agrees with (Kong et al, 2014), whom they found the mean hemoglobin level of ALL patient was 8.91g/dL and (Gupta et al, 2021) which reported that the mean hemoglobin level of newly diagnostic ALL children was 7.3 g/dL.…”
Section: Discussionsupporting
confidence: 90%
“…In this study Hb was significantly higher after chemotherapy with an average moved from 7.6 to 11.0 mg/dl. This result agrees with (Kong et al, 2014), whom they found the mean hemoglobin level of ALL patient was 8.91g/dL and (Gupta et al, 2021) which reported that the mean hemoglobin level of newly diagnostic ALL children was 7.3 g/dL.…”
Section: Discussionsupporting
confidence: 90%